The Synthesis and Properties of TIPA-Dominated Porous Metal-Organic Frameworks - Hongru Fu (MDPI AG, 2021)
Metal-Organic Frameworks (MOFs) as a class of crystalline materials are constructed using metal nodes and organic spacers. Polydentate N-donor ligands play a mainstay-type role in the construction of metal−organic frameworks, especially cationic MOFs. Highly stable cationic MOFs with high porosity and open channels exhibit distinct advantages, they can act as a powerful ion exchange platform for the capture of toxic heavy-metal oxoanions through a Single-Crystal to Single-Crystal (SC-SC) pattern. Porous luminescent MOFs can act as nano-sized containers to encapsulate guest emitters and construct multi-emitter materials for chemical sensing. This feature article reviews the synthesis and application of porous Metal-Organic Frameworks based on tridentate ligand tris (4-(1H-imidazol-1-yl) phenyl) amine (TIPA) and focuses on design strategies for the synthesis of TIPA-dominated Metal-Organic Frameworks with high porosity and stability. The design strategies are integrated into four types: small organic molecule as auxiliaries, inorganic oxyanion as auxiliaries, small organic molecule as secondary linkers, and metal clusters as nodes. The applications of ratiometric sensing, the adsorption of oxyanions contaminants from water, and small molecule gas storage are summarized. We hope to provide experience and inspiration in the design and construction of highly porous MOFs base on polydentate N-donor ligands.